Clinical features and immune mechanisms directly linked to the altered liver function in patients with rheumatoid arthritis - Arias-de la Rosa, I; Ruiz-Ponce, M; Cuesta-López, L; Pérez-Sánchez, C; Leiva-Cepas, F; Gahete, MD; Navarro, P; Ortega, R; Cordoba, J; Pérez-Pampin, E; González, A; Lucendo, AJ; et al. (European journal of internal medicine, 2023)
•Liver alterations in RA can occur independently of obesity or diabetes.•NAFLD in RA is related to the systemic inflammatory burden, disease activity, and levels of autoantibodies.•Liver of RA patients might be characterized by inflammation due to the infiltration of T and B cells and macrophages.•ACPAs can directly act on hepatocytes.•The deleterious effects of methotrexate on the liver might depend on the concomitant presence of cardiovascular risk factors. The aim of this study was to explore the impact of arthritis on liver function using different approaches in vivo and in vitro. A cross-sectional study was performed on 330 non-obese/non-T2DM subjects: 180 RA patients, 50 NAFLD non-RA patients, and 100 healthy donors (HDs). A longitudinal study was conducted on 50 RA patients treated with methotrexate for six months. Clinical and laboratory parameters and markers of liver disease were collected. Mechanistic studies were carried out in both the CIA mouse model and hepatocytes treated with anti-citrullinated protein antibodies (ACPAs). RA patients have an increased risk of suffering from liver disease independent of obesity or T2DM. This risk was associated with factors such as insulin resistance, autoantibodies, inflammation, and component C3. Methotrexate treatment for six months was associated with liver abnormalities in those newly-diagnosed patients having CV risk factors. ACPAs induced a defective hepatocyte function, promoting IR and inflammation. The induction of arthritis in mice caused the infiltration of immune cells in the liver and increased inflammatory, apoptotic, and fibrotic processes. RA patients may experience mild to moderate liver inflammation due to the infiltration of T, B cells, and macrophages, and the action of ACPAs. This is independent of obesity or diabetes and linked to systemic inflammation, and disease activity levels. The negative effects of methotrexate on liver function could be restricted to the concomitant presence of cardiovascular risk factors. [Display omitted]